The effect of caesium alloying on the ultrafast structural dynamics of hybrid organic-inorganic halide perovskites - Gallop, Nathaniel P; Ye, Junzhi; Greetham, Gregory M; Jansen, Thomas L. C; Dai, Linjie; Zelewski, Szymon J; Arul, Rakesh; Baumberg, Jeremy J; Hoye, Robert L. Z; Bakulin, Artem A (Journal of materials chemistry. A, Materials for energy and sustainability, 2022)
Hybrid inorganic-organic perovskites have attracted considerable attention over recent years as promising processable electronic materials. In particular, the rich structural dynamics of these 'soft' materials has become a subject of investigation and debate due to their direct influence on the perovskites' optoelectronic properties. Significant effort has focused on understanding the role and behaviour of the organic cations within the perovskite, as their rotational dynamics may be linked to material stability, heterogeneity and performance in (opto)electronic devices. To this end, we use two-dimensional IR spectroscopy (2DIR) to understand the effect of partial caesium alloying on the rotational dynamics of the methylammonium cation in the archetypal hybrid perovskite CH 3 NH 3 PbI 3 . We find that caesium incorporation primarily inhibits the slower 'reorientational jump' modes of the organic cation, whilst a smaller effect on the fast 'wobbling time' may be due to distortions and rigidisation of the inorganic cuboctahedral cage. 2DIR centre-line-slope analysis further reveals that while static disorder increases with caesium substitution, the dynamic disorder (reflected in the phase memory of the N-H stretching mode of methylammonium) is largely independent of caesium addition. Our results contribute to the development of a unified model of cation dynamics within organohalide perovskites. Using advanced spectroscopic and photophysical techniques, we describe how the inorganic cage affects the rotation of the organic cations in caesium-alloyed hybrid inorganic-organic perovskites.